A Comparative Study of the Tolerance to Stress Response Under Spinal Anaesthesia in Diabetic Versus Non-Diabetic Patients - Saha, Prince; Shah, Bhavini Bhushan; Vazhakalayil, Subha Jose; Thakur, Aishwarya (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Activation of sympathetic nervous system, increase of catabolic hormone release and pituitary gland suppression are responses to surgical stress. Neural blockade via epidural or spinal anesthesia, intravenous administration of high-dose of strong opioid analgesics, and infusion of anabolic hormones such as insulin are three main methods for balancing stress responses to surgery. However, there are conflicting reports about the extent of autonomic disturbances occurring after inducing spinal anesthesia in diabetic patients due to underlying autonomic neuropathy. METHODOLOGY: An observational cohort study was conducted in an operative room of a tertiary health care center involving 25 diabetic patients and 25 non-diabetic patients to evaluate the tolerance to stress. The diabetic patients undergone an exercise tolerance test to evaluate for postural hypotension which would indicate presence of autonomic neuropathy. Stress parameters such as heart rate, mean blood pressure, blood glucose level, and temperature were measured at regular intervals pre, peri- and post-operatively. RESULTS: Intraoperative heart rate, mean blood pressure, and blood glucose level were high in diabetic patients with autonomic neuropathy (p≤0.05). Temperature was higher in diabetic patients with autonomic neuropathy initially (p≤0.05) and had a higher fall peri-and post-operatively (T=15 minutes, T=20 minutes, and T=after surgery). A significant differences in the parameters of stress response were observed in diabetic patients with autonomic neuropathy. CONCLUSION: By understanding the correlation between stress-response in diabetic patients with autonomic neuropathy peri-operatively will help the anesthetist to provide customized services to every patient